Immature functional development of lumbar locomotor networks in adult Irf8−/− mice - Yazawa, Itaru; Yoshida, Yuko; Yoshimi, Ryusuke; Ozato, Keiko (Frontiers in Neuroscience, 2024)
To date, research on the role of the brainstem and spinal cord in motor behavior has relied on in vitro preparations of the neonatal rodent spinal cord, with or without the brainstem; their spatial and temporal scope are subject to technical limitations imposed by low oxygen tension in deep tissues. Therefore, we created an arterially perfused in situ preparation that allowed us to investigate functional interactions in the CNS from the neonatal to adult period. Decerebrated rodents were kept alive via total artificial cardiopulmonary bypass for extracorporeal circulation; the plasma oxygen and ion components needed for survival were supplied through the blood vessels. Interferon regulatory factor 8 (IRF8) is a transcription factor that promotes myeloid cell development and stimulates innate immune responses. In the brain, IRF8 is expressed only in microglia and directs the expression of many genes that serve microglial functions. Recent evidence indicates that IRF8 affects behavior and modulates Alzheimer’s disease progression in a mouse model. However, whether this immune deficiency arising from the absence of IRF8 influences the development of the neuronal network in the spinal cord is unknown. We applied the above methodology to mice of all ages and electrophysiologically explored whether the absence of IRF8 influences the development of lumbar central pattern generator (CPG) networks. In mice of all ages, bilateral neuronal discharges by the normal CPG networks activated by the modulated sympathetic tone via descending pathways at high flow rates became organized into discharge episodes punctuated by periods of quiescence. Similar discharge episodes were generated by the adult CPG networks (≥P14 days) activated by drug application. However, discharge episodes elicited by activating the neonatal-juvenile CPG networks (<P14 days) occurred alternately on the left and right sides. Interestingly, discharge episodes elicited by the CPG networks in adult IRF8 knockout mice (P11–12 weeks) consisted of those elicited by the CPG networks of both periods. Thus, it was suggested that growing up with immunodeficiency due to loss of IRF8 might interfere with the normal development of functions exerted by the lumbar CPG network because IRF8 plays a role in the normal development of the lumbar CPG network.